I disturbi del neurosviluppo: verso un modello clinico integrato - Flavia Morfini (Phenomena Journal)
The purpose of the research work of the writer is the gradual development of an integrated clinical model for the treatment of high-functioning autism. The analysis for the constitution of this model has started from the identification of a specific logic with which to integrate three models: cognitive behavioral, Gestalt and model deriving from the applied analysis of behavior (ABA).  This logic has materialized in the identification, through an analysis process based on the examination of the scientific literature and on their clinical experience, of what they been defined as the active ingredients of each of these disciplines, that is, the variables most involved in the efficacy of treatment for level 1 autism. The present work therefore constitutes the next step in this reasoning. The focus is on the active ingredients of the Aba. We intend to carry out a rigorous analysis of the function of behavior in an integrated perspective for the treatment of high-functioning autism. Understanding the function of behavior naturally has an evident clinical significance as it is the basis of the therapeutic project in all clinical models, even though it is addressed with different languages and tools. In gestalt therapy the focus is on contact needs and how those needs are blocked; in behavioral cognitive orientation the emphasis is on mental patterns as behavior triggers, while in the applied analysis of behavior the single aspects of a behavioral process are examined, defining the latter functional analysis. Therefore, an analytical and systematic vision of the function of behavior is present in Aba. It represents a valuable contribution to an evidence-based model which is for this reason one of the central aspects of the model I am working on.